AN OBSERVATION OF 10-MONTHS TREATMENT OF CLASS III MALOCCLUSION USING BEGG TECHNIQUE APPLIANCE (Case Report) - Novianty, Shella Indri (Ikatan Ortodontis Indonesia, 2013)
Background: On Angle's Class III malocclusion, reverse overjet is created either b malpositions of the upper and lower incisor, with or without a skeletal factor contribution. To achieve the proper inter-incisal relationship, the upper anterior will be protracted and lower anterior were retracted. Objectives: To report a 10 months treatment of class III malocclusion using Begg aplliance. Case Report and Management: A 19 years old woman was diagnosed as Angle's Class III malocclusion with skeletal class III, retrognatic maxilla, prognatic mandible, bidental protrusive, overjet: -3,4 mm, overbite 3,64 mm, TMJ's Clicking on the left side, anterior cross bite, and teeth malpositions. First lower bicuspids were extraction at the upper for the treatment. The treatment has been started on April 2012 using Begg appliance. The upper anterior were 2 mm protracted and the lower anterior were 2 mm retracted. The aims of stage I were achieved by multilooped arch wire, anchorage bend 45°, circle loops, and class III intermaxillary elastics 5/16" 4 oz. Result: Afetr 10 months treatment showed improvement in profile and skeletal appraisal, none of clicking at TMJ, anterior cross bite was corrected with overjet 2 mm and overbite 1,5 mm, and teeth malpositions were corrected. Nowadays, this case is in progress of stage 2. Conclusion: Observation of 10 months treatment showed that Begg technique has the required versatility to treat Class III malocclusion.